Brides of Rough Creek Texas: Home to Texas - Book 2 - Warner, Kaki (New York : Jove, 2021)
Honorably discharged from the Army due to an injury in the field, Lieutenant KD Whitcomb heads home to the Four Star Ranch where the horses help her heal as well as warrant officer Richard Murddock who helps her--and her heart--get back in the saddle again.
Keywords: Veterans -- Fiction; Horses -- Fiction; Ranch life -- Fiction; Romance fiction; Western fiction